Screening of compound-formulated Bacillus and its effect on plant growth promotion - Shen, Yuying; Yang, Huan; Lin, Zheng; Chu, Linglong; Pan, Xiao; Wang, Yu; Liu, Wenbo; Jin, Pengfei; Miao, Weiguo (Frontiers in Plant Science, 2023)
Bacillus bacteria can produce extremely abundant secondary metabolites useful for biocontrol, especially when maintaining plant root microecology and for plant protection. In this study, we determine indicators of six strains of Bacillus for colonization, promotion of plant growth, antimicrobial activity, and other aspects, with the aim to obtain a compound bacteriological agent to construct a beneficial Bacillus microbial community in plant roots. The results showed there was no significant difference in the growth curve of the six strains of Bacillus over 12 h. However, strain HN-2 was found to have the strongest swimming ability and the highest bacteriostatic effect of n-butanol extract on blight-causing bacteria, Xanthomonas oryzae pv. oryzicola. The hemolytic circle produced by the n-butanol extract of strain FZB42 was the largest (8.67 ± 0.13 mm) and had the greatest bacteriostatic effect on the fungal pathogen, Colletotrichum gloeosporioides, with a bacteriostatic circle diameter of 21.74 ± 0.40 mm. Strains HN-2 and FZB42 can rapidly form biofilms. Time-of-flight mass spectrometry and hemolytic plate tests showed that HN-2 and FZB42 strains can have such significantly different activity because of their ability to produce large quantities of lipopeptides (surfactin, iturin, and fengycin). Different growth-promoting experiments revealed that strains FZB42, HN-2, HAB-2, and HAB-5 all had better growth-promoting potential than the control; therefore, these four strains were compounded in an equal ratio and then used to treat pepper seedlings through root irrigation. We found an increase in the stem thickness (13 %), leaf dry weight (14 %), leaf number (26 %), and chlorophyll content (41 %) of pepper seedlings treated with the composite formulated bacterial solution compared to the optimal single bacterial solution treatment. Further, for several of these indicators, the composite solution-treated pepper seedlings increased by an average of 30 % compared to the control water treatment group. In conclusion, the composite solution obtained by compounding strains FZB42 (OD600=1.2), HN-2 (OD600=0.9), HAB-2(OD600=0.9) and HAB-5 (OD600=1.2) in equal parts highlights the advantages of a single bacterial solution, including achieving good growth promotion and antagonistic effects against pathogenic bacteria.